Pengaruh Perlakuan Silane Dan NaOH Pada Permukaan Serat Kontinyu Limbah Epulur Sagu (Metroxylon Sp) Terhadap Daya Serap Air Dan Kekuatan Bending - Matheus, Josef; Irawan, Yudy Surya; Soenoko, Rudy (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2013)
Utilization of composite materials at this moment is growing, along with increasing use of these materials in widespread ranging from a simple household appliances to the industrial sector. The purpose of this study is to determine the mechanical properties and water absorption of continuous fiber composites sago pith waste, on a percentage variation in respectivevolume fraction 10%, 30%, and 50%. The fiber is treated by immersion treatment with 5% NaOH alkaline 2 hours and 2% solution of silane for 30, 60, and 90 minutes. Mechanical properties of the composite test results that at 47.37 MPa tensile strength and bending strength of 72.27 MPa with a percentage of the volume fraction (50%), under fiber soaking time (30 minutes) are in the same value. The smaller the value of water uptake, it is contained in immersion treatment of sago pith waste continuous fibers with a percentage of 50% and the volume fraction of fiber soaking time 90 minutes.Keywords: Composites, mechanical properties, water absorption, sago pith waste, volume fraction